2008
DOI: 10.1021/ac801215c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene glycol)-Based Stable Isotope Labeling Reagents for the Quantitative Analysis of Low Molecular Weight Metabolites by LC−MS

Abstract: Stable isotope labeling (SIL) in combination with liquid chromatography-mass spectrometry is one of the most widely used quantitative analytical methods due to its sensitivity and ability to deal with extremely complex biological samples. However, SIL methods for metabolite analysis are still often limited in terms of multiplexing, the chromatographic properties of the derivatized analytes, or their ionization efficiency. Here we describe a new family of reagents for the SIL of primary amine-containing compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 29 publications
2
35
0
1
Order By: Relevance
“…To date, several CIL reagents have been developed to quantify organic amines, carboxylic acids, carbonyl compounds and some other types of metabolites with varying degrees of performance [1,4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These research activities are mainly driven by the need of dealing with different classes of metabolites; a universally applicable derivatization reagent for LC-MS is not available at the present.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several CIL reagents have been developed to quantify organic amines, carboxylic acids, carbonyl compounds and some other types of metabolites with varying degrees of performance [1,4,5,[7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These research activities are mainly driven by the need of dealing with different classes of metabolites; a universally applicable derivatization reagent for LC-MS is not available at the present.…”
Section: Introductionmentioning
confidence: 99%
“…For their use, the products were dissolved in acetonitrile (HPLC supra gradient grade, Biosolve), divided into 1 μmol portions, vacuum dried and stored at −80°C until use. Pentafluorophenyl-activated PEG (mediumPEG, 4 ethylene oxide units) esters containing zero or five 13 C atoms (unlabeledmediumPEG, 13 C 5 -mediumPEG) were synthesized as described previously [29], dissolved in acetonitrile, divided into 1 μmol portions, vacuum dried and stored at −80°C until use.…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…We recently showed that PEG derivatization may also be useful in enhancing the ionization efficiency of small molecules such as amino acids, as well as to increase their hydrophobicity allowing analysis by reversed-phase LC-MS [29]. In addition, PEG ether functionalities may be protonated which could affect the ETD and CID pattern of derivatized DES [19,35,36].…”
Section: Etd Versus Cid Of Des Derivatized With Peg Molecules Of Diffmentioning
confidence: 99%
See 1 more Smart Citation
“…Unlike other chemical derivatization schemes where the main purpose was to introduce a mass tag to the metabolites for quantitative metabolite or metabolome analysis [21][22][23][24][25][26][27][28], dansylation can not only effectively introduce an isotope tag for accurate metabolite quantification, but also improve the chromatographic retention of the metabolites in reversed-phase LC and enhance the efficiency of electrospray ionization (ESI). In our previous work, sensitive detection of metabolites from human urine samples was demonstrated.…”
Section: Introductionmentioning
confidence: 99%